The Implementation of Performance Assessment Instruments to Enhance Students’ Collaboration and Communication Skills - Nia Sumiyati; Undang Rosidin; Agus Suyatna (Jurnal Pembelajaran Fisika, 2019)
This research aims to describe the relationship between student performance in physics learning based practicum on students' collaboration and communication skills of senior high school students. This study is quasi-experiment research. This study also tested the validity and reliability of the assessment instruments, and for data tested by using correlation test. The conclusion of this study is that there is no relationship between student performance on physics practicum based learning with students' collaboration and communication skills. Keywords: collaboration skill, communication skill, performance assesment DOI: http://dx.doi.org/10.23960/jpf.v7.n1.201904